Potential of Shells as a Source of Calcium - Suprijanto, Jusup; Widowati, Ita (Universitas Diponegoro, 2024)
Shellfish are also known as by-products, namely production results that are not utilized or not consumed, where the value of this by-product can be increased/added through a process known as Reduce-Reuse and Recycle (3R). This research aims to determine the potential of shellfish as a source of calcium. Samples of clams (Paphia undulata), blood clams (Tegillarca granosa), and Asian Moon Scallop (Amusium pleuronectes) were obtained from Tambak Lorok Fish Auction Place, Semarang; then taken to the Marine Biology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Diponegoro to have the shells, and air dry until dry after drying the shell. Calcium and mineral content were analyzed using the XRF method at the Integrated Laboratory, Universitas Diponegoro. The results of the study showed that the calcium (CaO) content of the three shellfish was the lowest in the clam (P. undulata) at 45.79%, then the Asian moon Scallop (A. pleuronectes) at 45.89%, and the highest in the blood cockle T. granosa namely 92.41%. It can be concluded that the shells of clams, blood clams, and Asian Moon Scallops contain high levels of calcium and minerals, which have the potential to be used as an additional ingredient in concrete/paving blocks and fish feed.